2023
DOI: 10.1038/s41419-023-05620-7
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the reverse cholesterol transport pathway to favor differentiation of monocyte-derived APCs and antitumor responses

Abstract: Lipid and cholesterol metabolism play a crucial role in tumor cell behavior and in shaping the tumor microenvironment. In particular, enzymatic and non-enzymatic cholesterol metabolism, and derived metabolites control dendritic cell (DC) functions, ultimately impacting tumor antigen presentation within and outside the tumor mass, dampening tumor immunity and immunotherapeutic attempts. The mechanisms accounting for such events remain largely to be defined. Here we perturbed (oxy)sterol metabolism genetically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…This is because oxysterols such as 27-HC secreted by tumor cells signi cantly inhibit SREBP2 and activate LXR, thereby leading to T cell cholesterol de ciency and driving T cell depletion and dysfunction, especially for cytotoxic T cells 9 . Other studies have shown that SULT2B1b derivatives promote the activation and differentiation of monocyte-derived cells by interfering with LXR signals, thus delaying tumor growth 10 . Moreover, cholesterol-rich TME can also increase the expression of immune checkpoints 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This is because oxysterols such as 27-HC secreted by tumor cells signi cantly inhibit SREBP2 and activate LXR, thereby leading to T cell cholesterol de ciency and driving T cell depletion and dysfunction, especially for cytotoxic T cells 9 . Other studies have shown that SULT2B1b derivatives promote the activation and differentiation of monocyte-derived cells by interfering with LXR signals, thus delaying tumor growth 10 . Moreover, cholesterol-rich TME can also increase the expression of immune checkpoints 11 .…”
Section: Introductionmentioning
confidence: 99%